Electrochemical recovery of metal copper in microbial fuel cell using graphene oxide/polypyrrole cathode catalyst. (15th December 2020) - Rikame, Satish S.; Mungray, Alka A.; Mungray, Arvind K.
Summary: The graphene oxide and conducting polypyrrole composite modified cathodes is prepared by electro‐polymerization. The microscopic images of the graphene oxide/polypyrrole composite confirmed that the active carbon support was entirely covered by polypyrrole. The ascertain graphene oxide/polypyrrole composite is characterized through Fourier transform infrared spectroscopy and X‐ray diffraction. The graphene oxide/polypyrrole composite exhibited higher open circuit voltage. The Cyclic voltammetry and Electrochemical impedance spectroscopy analysis suggest the improved performance of graphene oxide/polypyrrole as compared to polypyrrole and bare graphite in terms of lower internal resistance and better electro‐catalytic activity. The large amount of active spots with continual hauler networks of graphene oxide/polypyrrole compound showed an improved microbial fuel cell power output of 600.25 mW/m 3 . Graphene oxide/polypyrrole as a cathode catalyst is proved to be sustainable for the effective remediation of metal copper. The maximum copper recovery is 98.88% with simultaneous % Chemical oxygen demand reduction of 98.6%. These research findings suggest the possible knowledge for the synthesis of graphene based composites by electro‐polymerization. Abstract : This article treats the metal containing wastewater with Graphene Oxide/Polypyrrole (GO/PPy) modified cathode using Microbial fuel cell (MFC). The cathode composite shows the improved performance in terms of metal recovery, power density and quite stable for the prolonged operation. The GO/PPy composite shows the possible sustainable approach for the remediation of metals and possible alternative to conventional carbonaceous material.